MINERAL INCLUSIONS IN THE LATE BRONZE AGE METAL OBJECTS OF SOUTHERN TRANSURALS - M.N. Ankushev; I.A. Blinov; I.P. Alaeva; N.B. Vinogradov; F.N. Petrov; P.S. Ankusheva (Минералогия)
The paper is devoted to the determination of copper raw material types based on the analysis of mineral inclusions and the composition of metal objects from the Late Bronze Age settlements of the Southern Transurals (XIX–XIII centuries BC). The composition of alloys, inclusions of sulfides, oxides and metals of objects was established by scanning electron microscopy. The composition of objects is dominated by copper and tin bronze, with a subordinate role of arsenic bronze. The presence of chalcocite and bornite inclusions in most objects indicates the use of rich ores from secondary sulfide enrichment zone. In comparison with analogs, the low total amount of sulfides in the Southern Transuralian metal objects may indicate the use of mixed oxide and sulfide concentrates. The high Se and Te concentrations of sulfides are indicative of using of ores of volcanic-hosted massive sulfide or skarn deposits.